Alpha Mangosteen Effect on MDA Level and the Pancreatic Morphology Rattus norvegicus (Berkenhout, 1769) Induced by Alloxan: Alpha Mangosteen Effect on MDA Level and the Pancreatic Morphology - Wulandari, Devyana Dyah; Mufidah, Zumrotul; Ersam, Taslim; Wulansari, Devyani Diah; Corpuz, Alfredo Vita (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2020)
The alpha mangosteen compound is a single compound isolated from rind extract Garcinia mangostana Linn, known to have antidiabetic bioactivity. This research aimed to determine the effect of the α-mangosteen compound on Malondialdehyde (MDA) and rats pancreatic tissue induced with type 2 Diabetes mellitus. Twentyfour Wistar male rats were divided into four groups, each group consisting of six rats. The first group was set as a positive control, rats injected with a single dose of 150 mg kg–1 alloxan. The second group was the negative control, which means that no treatment. The third group was injected with a single dose of 150 mg kg–1 alloxan and α-mangosteen compound 10 mg kg–1, while the last group was injected with a single dose of 150 mg kg–1 alloxan and 10 mg kg–1 standard drug glibenclamide. All groups were monitored for 3 wk, and blood sugar levels were measured using a Glucose meter. Blood samples were taken for the measurement of MDA, and the pancreas organ was removed for histological study. This research showed that the difference of MDA level between α-mangosteen compound treatment and glibenclamide was only 0.481 8. It means that the α-mangosteen compound can reduce MDA levels alike the standard drug glibenclamide capabilities. Islets of Langerhans on normal pancreatic mice (control (-)) looked filling full with the endocrine cells spread throughout the pancreas. While at the control group (+) there was a roomempty space (fewer the number of beta cells) in islets of Langerhans. On the treatment groups, those were giving α-mangosteen, and drug compounds standard (glibenclamide) showed improvement in Langerhans β cells compared with a treatment group of diabetic mice (control+). The administration of α-mangosteen compound 10 mg kg–1 BW able to decrease MDA level 1.204 7 nmol dl–1. While based on histological observations of the pancreas showed that the alpha mangosteen treatment group showed improvement of Langerhans β cells compared to the diabetic rat group (positive control)